Improvement in mechanical and ablation properties of carbon/carbon composites with nanofilamentous carbon and CeC2. (October 2022) - Deng, Hailiang; Li, Jiaqing; Zheng, Jinhuang; Zhang, Shihong; Deng, Xiangong; Song, Guangsheng; Li, Kezhi
Abstract: Nanofilamentous carbons (NFCs) and CeC2 NF@NFC core-shell structures reinforced carbon/carbon composites were fabricated using chemical vapor infiltration via adding CeCl3 into preforms. The NFCs and CeC2 NF@NFCs constructed reinforcing bridges across the fiber/matrix interface and matrix with proper CeCl3 contents. The flexural and interlaminar shear properties were remarkably improved due to the synergistic reinforcements of the nanofilaments and CeC2 particles. The inhibition of matrix damage by the nanofilaments together with a thickened rough laminar pyrocarbon and rapid heat dissipation alleviated annular matrix oxidation and denudation. Higher CeCl3 content increased the oxidation channels and active sites and then oxidation ablation. Graphical Abstract: The reinforcing effect of NFCs and CeC2 NF@ /NFCs improves the mechanical properties. The inhibition of matrix cracking and exfoliation by NFCs and CeC2 NF@NFCs together with the thickened RL PyC and rapid heat dissipation alleviate the annular matrix oxidation and then denudation, thus improve the ablation resistance. ga1 Highlights: Nanofilamentous carbons (NFCs) and CeC2 NF@NFCs are grown by adding CeCl3 . CeCl3 and nanofilaments favor the formation of rough laminar pyrocarbon (RL PyC). Nanofilaments act as reinforcing bridges across the matrix and fiber/matrix interface. Nanofilaments and thickened RL PyC relieve annular matrix oxidation and denudation.